Übersetzer- und Dolmetscherausbildung in Finnland - Liefländer-Koistinen, Luise (Glottodidactica, 1999)
Translator education in Finland has been on university level since 1980. There are four Schools of Translation belonging to the University of Helsinki (Kouvola), University of Joensuu (Savonlinna), University of Tampere and University of Turku. Students have to study appr. 5 years to get the degree of Master of Arts. They usually study at least two languages - they can choose between English, Russian, German, Swedish or French as their main subject, and there is the choice between several other languages or special subjects (like: language of law, commerce, intercultural communication etc.) as a second or third subject. Finnish translators get jobs in the EU, the business sector or administration.